Breaking through : how female athletes shattered stereotypes in the roaring twenties - Macy, Sue (National Geographic, 2020)
"Macy offers a rare and fascinating glimpse into the journey of women's rights through the lens of women in sports during the pivotal decade of the 1920s. With elegant prose, poignant wit, and fascinating primary sources, Macy explores the many hurdles presented to female athletes as they stormed the field, stepped up to bat, and won the right to compete in sports. Featuring bold and talented heroines, this book documents how the social issues and morals of the decade--from politics to segregation to the media--helped shape the changing narratives around women and alter the course of history entirely. It is a fascinating window into a rich and seldom explored history, and also a topical reminder of the many discussions surrounding femininity and the role of women that continue today."--Amazon.com